Performance of a new passive damper for seismic protection of structures / Khaled Ghaedi - Khaled , Ghaedi (2020)
Passive energy dissipation devices have been successfully implemented in buildings around the world to reduce structural responses primarily to earthquakes, wind and other dynamic loads. Unlike active and semi-active control systems, passive systems make use of control devices that serve secondary functions. They are connected to structural members to increase structural damping without the use of external forces. The aim of this research is to introduce and investigate the performance of a new passive damper device called bar damper (BD), which is made of a number of solid bars sandwiched between two plates. The concept, placement and material properties of the device are initially presented and described. Subsequently, the test setup and loading procedures are presented and the performance of the proposed damper is assessed. For this purpose, two experimental test stages were implemented with cyclic loading applied. In the first stage, the BD was tested on its own keeping in view a number of design parameters, including the height, diameter and number of solid bars used in the design of the damper device. In the second stage, the bar damper was installed in a structural frame and experimentally tested under cyclic loading to monitor the performance of the device and frame structure equipped with the BD device. The results obtained in the first stage confirmed that the BD specimens exhibited stable hysteretic behavior with a smooth change from elastic to inelastic regime. The experiments also showed that the BD specimens were very efficient in energy dissipation and demonstrated appropriate tolerance in cumulative displacement as well as very ductile performance without significant strength or stiffness degradation. In addition to the experimental study, a finite element (FE) analysis was also done. The analysis results were compared with the experimental results and these were in good agreement. In accordance with the experimental and FE analysis outcomes, a simplified bilinear model of the BD was proposed to enhance practical use of the device. Moreover, theoretical equations of the damper device were derived based on its plastic mechanism. It is noted that the strength and ductility of the device estimated from the theoretical equations corresponded well with the results obtained from the experiments done in the first stage. It is also interesting to mention that it was possible to achieve suitable performance of the device in terms of increasing energy dissipation level, strength, stiffness and ductility either with the proposed formulas or according to the FE analysis. The results from the experiments on the test frames conducted in the second stage also proved the positive effect of the BD devices on the overall performance of the test frame where strength, stiffness, deformation capacity and energy dissipation level of the frame increased. Moreover, a FE model of the tested frames was developed for further investigation. Overall, it is believed that since the proposed damper achieved excellent performance, it can be adopted for practical use by structural designers to protect new and existing buildings and bridges.